J. Leibold (2007). Reconfiguring Chinese nationalism: How the Qing frontier and its indigenes became Chinese. Nueva York: Palgrave MacMillan. 271 pp. - Olivieri, Chiara (Estudios de Asia y África, 2019)
J. Leibold (2007). Reconfiguring Chinese nationalism: How the Qing frontier and its indigenes became Chinese. Nueva York: Palgrave MacMillan. 271 pp.